Crop Wild Relative Conservation and Use - Maxted, N (CABI, 2014)
Crop wild relatives (CWR), which are wild species closely related to crops, are a neglected global natural resource; yet they make a concrete contribution to global wealth creation and food security (estimated at US$350 million per year in 1986 in the USA alone). CWR genetic diversity is severely threatened by habitat loss, fragmentation and simplification, the impact of invasive species, overexploitation and global change, but the diversity of CWR is not adequately conserved, either in situor ex situ. In recent years, slowly but steadily, the science of CWR conservation has been developed, applying both in situand ex situtechniques, in parallel with their growing exploitation as gene donors for the broad range of crops. Especially the EC-funded PGR Forum project, which this volume grew out of, has made significant methodological advances. The project culminated in the First International Conference on Crop Wild Relative Conservation and Use, which was held in Sicily, Italy, in September 2005. As the Conference title suggests, the scope was broader than simply reporting the products of a European project – for the first time, it provided a platform for CWR scientists, potential users and other stakeholders to debate the broad range of issues relating to CWR conservation and use. It aimed to provide a comprehensive review of CWR conservation and use methods, highlight exemplar case studies and draw attention to new initiatives.